THE ROLE OF AI TOOLS IN ENHANCING ANALYTICAL AND CRITICAL THINKING SKILLS IN UNIVERSITY STUDENTS - Gʻayrat Muxtorovich Sultonqulov, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract In  the  rapidly  changing  landscape  of  higher  education,  the  integration  of Artificial  Intelligence  (AI)  tools  presents  a  transformative  opportunity  to  boost students' analytical and critical thinking skills. This article elucidates the various AI applications  utilized  in  universities,  their  impact  on  learning  outcomes,  and  the pedagogical  strategies  that  can  be  deployed  to  maximize  their  effectiveness.  By examining case studies, theoretical frameworks, and empirical research, this article aims  to  provide  a  comprehensive  overview  of  how  AI  tools  can  support  the development of essential skills necessary for success in an increasingly complex world.